Dampak Tiktok Terhadap Penurunan Etika Generasi Muda - Zahrotun Nahla; Bagus Setiawan; Anisa Fitri Nabila (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to describe the impact of using TikTok social media on the ethics and behavior of the younger generation using the literature study method. Data is collected from various sources, including journal articles, books, and other scientific publications. The results of the analysis highlight that the use of TikTok can lead to a decrease in ethical and inappropriate behavior among the younger generation. Unethical content such as exposing, violence, and discrimination can be found on these platforms, affecting moral values ​​and social norms. Proposed solutions include increased awareness of digital education, a more active role for parents, as well as technology companies' responsibility in content moderation. This research provides important insights into the negative impacts of TikTok and identifies steps that can be taken to overcome these challenges in improving the ethics and behavior of young people.